A Framing Analysis of Consultation Submissions on the WHO Global Strategy to Reduce the Harmful Use of Alcohol: Values and Interests - Chiara Rinaldi; May CI van Schalkwyk; Matt Egan; Mark Petticrew (Kerman University of Medical Sciences, 2022)
Background  In response to the magnitude of harms caused by alcohol, the World Health Organization (WHO) Global Strategy to Reduce the Harmful Use of Alcohol (GAS) was endorsed in 2010. We analysed submissions to the 2019 WHO consultation on the implementation of the GAS to identify how different stakeholders frame alcohol use and control; and to assess how stakeholders engage with the consultation process, with possibly harmful consequences for public health policy. Methods  All submissions from WHO Member States, international organisations, non-governmental organisations (NGOs), academic institutions and private sector entities were identified and used as data for an inductive framing analysis. This involved close reading and data familiarisation, thematic coding and identifying emergent framings. Through the analysis of texts, framing analysis can give insights into the values and interests of stakeholders. Because framing influences how issues are conceptualised and addressed, framing analysis is a useful tool to study policy-making processes.Results  We identified 161 unique submissions and seven attachments. Emerging frames were grouped according to their function: defining the problem, assigning causation, proposing solutions, or justifying and persuading. Submissions varied in terms of the framing they deployed and how this was presented, eg, how the problem was defined. Proposed policy solutions also varied. Targeted solutions emphasising individual responsibility tended to be supported by industry and some Member States. Calls for universal regulation and global mobilisation often came from NGOs and academia. Stakeholders drew on evidence and specific value systems to support the adoption of certain problem and solution ideas and to oppose competing framing. Conclusion  Alcohol control is a contested policy field in which different stakeholders use framing to set the agenda and influence what policy solutions are considered legitimate. WHO should consider which interests are served by these different framings and how to weigh different stakeholders in the consultation process.